The Effects of Raw and Processed Mucuna pruriens Seed Based Diets on the Growth Parameters and Meat Characteristics of Benin Local Guinea Fowl (Numida meleagris, L) - Dahouda, M.; Toleba, V.S.; Youssao, A.K.I; Ali, A. A. Mama; Dangou-Sapoho, R.K.; Ahounou, S.G.; Hambuckers, A.; Hornick, J.L. (International Journal of Poultry Science, 2009)
The aim of the present study was to compare the growth characteristics of guinea fowl fed on Mucuna pruriens (pica-pica, cow-hitch plant, cowhage, velvet bean, devil bean) seed with a control group at both starting and growing phases in extensive production in tropical Africa country (Benin). It was also attempt at determining meat traits and ascertains meat eventual contamination by L-Dopa for safely human consumption. To measure these effects, 20 % raw or processed (cooked or toasted) Mucuna seed were incorporated in guinea fowl diets. Mucuna seed processing reveals changes in ash, NNE, CP, Crude fibre and EE contents. Cooking markedly reduced L-Dopa level by 52 %. Roasting was also effective but at a lower extent, i.e., 36%. Feed intake showed that raw Mucuna seed significantly impaired feed intake but processing improved the condition. Mucuna depressing effect on growth parameters were less affective on adult birds than on keets. Lowest eviscerated carcass weights, dressing percentage and cut parts were recorded in group fed on raw Mucuna seed. The thigh-drumsticks, heads and legs of the male were found to be significantly heavier than those of the female. Differences between sexes were also noticed in liver, heart and gizzard. The liver and heart weights were significantly reduced in birds fed on raw seeds while the gizzard weights were increased significantly in processed seeds diets. Mucuna seed intakes did not change meat quality (pH24 and water holding capacity). Analyses of muscle, liver and kidney did not reveal the presence of L-Dopa in meat. The conclusions are that processed Mucuna seed can replace soybeans up to 20% for extensive guinea fowl production and contribute to diminish dependence to conventional protein for small holders.